Effect of Extraction Time on the Yield and Color Characteristics of White Pepper (Piper Nigrum L.) Oleoresin - Damanik, Annisa Purnamasari; Surya, Satria Adi; Mulianda, Pratiwi (Journal of Agriculture, 2025)
This study investigates the effect of extraction time on the yield and color characteristics of white pepper (Piper nigrum L.) oleoresin using the microwave-assisted extraction (MAE) method compared to conventional maceration. White pepper powder was extracted with 96% ethanol at four MAE durations (30, 60, 90, and 120 minutes) under a maximum controlled temperature of 50 °C, with maceration for 420 minutes as control. Results showed that MAE at 120 minutes produced the highest yield (10.370%), followed by 90 minutes (9.457%), 30 minutes (8.760%), and 60 minutes (8.323%). Conventional maceration yielded 8.610%, which was lower than MAE at 30 and 90 minutes, indicating higher efficiency of MAE even at shorter durations. Color analysis using CIELAB and RGB systems revealed that MAE at 90–120 minutes yielded brighter oleoresin (L > 56) compared to maceration (L = 53.33), while chromatic values (a and b) remained stable. Linear regression analysis showed a strong positive correlation between extraction time and yield (y = 0.1058x; R² = 0.8819), indicating that each additional minute increased yield by ~0.1058%. The findings suggest that MAE is a time-efficient method that enhances both yield and color quality of white pepper oleoresin, with optimal results obtained at 90–120 minutes.